Implementasi Imarah Masjid Besar Syuhada Lamgugob, Syiah Kuala, Kota Banda Aceh - Cut Aisyah Nur Ulayya; Roviana Roviana; Khairul Habibi (Khulasah : Islamic Studies Journal, 2026)
This study aims to analyze the implementation of imarah at the Syuhada Lamgugob Grand Mosque in Syiah Kuala District, Banda Aceh City, and to identify the factors that support and hinder its implementation. This is a qualitative study conducted using a descriptive approach. Data were collected through observation and in-depth interviews with the Imum Syiek of the Syuhada Lamgugob Grand Mosque and with several mosque management. The results indicate that two main components of imarah implementation have been carried out effectively: physical imarah and non-physical imarah. Physical imarah is realized through the construction and maintenance of the mosque’s facilities and infrastructure, while non-physical imarah is realized through various religious, educational, social, and community service programs, such as Maghrib and Subuh halaqahs, the Al-Qur’an Education Center (TPA), and the Al-Qur’an Study Center (TPQ), The successful implementation of imarah is due to the commitment of the management, high participation from the congregation, the availability of adequate facilities and infrastructure, and financial support from the community and donors. On the other hand, factors hindering the implementation of imarah include a lack of congregational participation, a shortage of human resources in the management, and a lack of coordination among management departments. This study found that several strategic steps can be taken to sustainably establish the mosque as a center for worship, education, da’wah, and community empowerment. These strategic steps include improving mosque management, hiring more administrators, increasing the involvement of the younger generation, and enhancing the internal communication system.